Mortalin overexpression predicts poor prognosis in early stage of non–small cell lung cancer - Jie Sun; Shuan-Long Che; Jun-Jie Piao; Ming Xu; Li-Yan Chen; Zhen-Hua Lin (Tumor Biology, 2017)
Mortalin is a member of the heat shock protein 70 family, which is involved in multiple cellular processes and may play key roles in promoting carcinogenesis. This study attempted to identify the clinical consequences of Mortalin overexpression and its roles in the prognostic evaluation of non–small cell lung cancer. A total of 120 non–small cell lung cancer samples paired with the adjacent non-tumor tissue samples and 10 normal lung tissues were selected for immunohistochemical staining for Mortalin. The localization of Mortalin was detected in A549 non–small cell lung cancer cells using immunofluorescence staining. The correlations between Mortalin overexpression and the clinical features of non–small cell lung cancers were evaluated using the chi-square test. The survival analysis was calculated via the Kaplan–Meier method and the Cox proportional hazard models. Our studies suggested that Mortalin exhibited a primarily cytoplasmic staining pattern in the non–small cell lung cancers. The rate of strongly positive Mortalin expression was higher in the non–small cell lung cancer samples than in the adjacent non-tumor samples or in normal lung tissues. Mortalin overexpression was significantly correlated with high histological grades, advanced stages, lymph node metastases, and lower disease-free survival and overall survival rates of the patients with non–small cell lung cancer. The survival analysis demonstrated that Mortalin overexpression was a significant independent prognostic factor in non–small cell lung cancer, especially for patients with early stage of non–small cell lung cancer. In conclusion, Mortalin is up-regulated in non–small cell lung cancer, and it may be a potential biomarker of prognostic evaluation and a molecular therapeutic target for patients with early stage of non–small cell lung cancer.